Effects of spin–orbit coupling and many-body correlations in STM transport through copper phthalocyanine - Siegert, Benjamin; Donarini, Andrea; Grifoni, Milena (Beilstein Journal of Nanotechnology, 2015)
The interplay of exchange correlations and spin–orbit interaction (SOI) on the many-body spectrum of a copper phtalocyanine (CuPc) molecule and their signatures in transport are investigated. We first derive a minimal model Hamiltonian in a basis of frontier orbitals that is able to reproduce experimentally observed singlet–triplet splittings. In a second step SOI effects are included perturbatively. Major consequences of the SOI are the splitting of former degenerate levels and a magnetic anisotropy, which can be captured by an effective low-energy spin Hamiltonian. We show that scanning tunneling microscopy-based magnetoconductance measurements can yield clear signatures of both these SOI-induced effects.
Keywords: anisotropy; copper phthalocyanine; magnetotransport; spin–orbit interaction; scanning tunneling microscopy (STM)